Constituents of essential oil from the root of Kadsura longipedunculata Fin. & Gagnep. collected in Kon Tum province - Thanh, Bui Van; Ban, Ninh Khac; Dai, Do Ngoc (Academia Journal of Biology, 2012)
The essential oil from the root of Kadsura longipedunculata Fin. & Gagnep. was prepared by steam distillation of fresh materials in a glass for 3h. The essential oils yields were 0.32% from the roots (in absolute dry material). The essential oils from K. longipedunculata analyzed by GC/MS consist of 27 constituents identified accounting more than 98.0% of the oil. The major components of the essential oil from the root of K. longipedunculata are: a-cadinol (41.0%), d-cadinene (7.6%), b-caryophyllene (7.4%). Less predominant constituents included a-amorphene (6.4%), acorenol B (4.4%), camphene (4.1%), borneol (3.6%), a-copaene (2.9%), bornyl acetate (2.6%), epi-bicyclophellandren (2.1%), b-gurjunene (2.1%), terpinolene-4-ol (1.9%), spathulenol (1.8%), caryophyllene oxide (1.7%), a-cadinen (1.6%) and b-selinene (1.3%) and all rest components with a content less than 0.1-0.9%.